Pengaruh Kepemimpinan Kepala Sekolah dan Kurikulum Merdeka terhadap Kinerja Guru - Wetri Wetri; Nur Ahyani; Suherman Suherman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to determine and describe the influence of the principal's leadership and the independent curriculum together on the performance of vocational teachers in Banyuasin III District. This research was carried out at SMK located in Banyuasin III District which consisted of 4 schools, namely, SMK Unggul Negeri 2 Banyuasin III, SMKN 1 Banyuasin III, SMKS Muhammadiyah Pangkalan Balai and SMKS PGRI Pangkalan Balai. This research is a type of quantitative research. The population in this study amounted to 116 teachers and principals. After calculating using the Slovin formula, the number of samples in this study was 55 people. Data collection techniques using questionnaires, questionnaires and documentation. Data analysis techniques use normality tests, linearity tests, multicollinearity tests, simple correlation analysis, multiple correlation analysis, simple regression analysis, t tests and F tests. The results of this study are There is a positive influence of the principal's leadership and independent curriculum together on teacher performance at SMK in Banyuasin III District by 81.2%. This can be seen from the results of the Fhitung>Ftabel test the influence can also be seen from the results of the thitung> ttabel test which means Ha3 is accepted and Ho3 is rejected. Keywords: Leadership; Principal; Independent Curriculum; Teacher Performance